Molecular Evolution and Interaction of Membrane Transport and Photoreception in Plants - Babla, Mohammad; Cai, Shengguan; Chen, Guang; Tissue, David T.; Cazzonelli, Christopher Ian; Chen, Zhong-Hua (Frontiers in Genetics, 2019)
Light is a vital regulator that controls physiological and cellular responses to regulate plant growth, development, yield and quality. Light is the driving force for electron and ion transport in the thylakoid membrane and other membranes of plant cells. In different plant species and cell types, light activates photoreceptors thereby modulating plasma membrane transport. Plants maximize their growth and photosynthesis by facilitating the coordinated regulation of ion channels, pumps and co-transporters across membranes to fine-tune nutrient uptake. The signal-transducing functions associated with membrane transporters, pumps and channels impart a complex array of mechanisms to regulate plant responses to light. The identification of light responsive membrane transport components and understanding of their potential interaction with photoreceptors will elucidate how light-activated signalling pathways optimise plant growth, production, and nutrition to the prevailing environmental changes. This review summarises the mechanisms underlying the physiological and molecular regulation of light-induced membrane transport and their potential interaction with photoreceptors in a plant evolutionary and nutrition context. It will shed new light on plant ecological conservation as well as agricultural production and crop quality, bringing potential nutrition and health benefits to humans and animals.